Patterns and determinants of age at first birth of women in Myanmar - Mya Thandar; Hlaing Hlaing Moe; Aye Aye Htwe (Asia-Pacific Sustainable Development Journal, 2021)
Fertility rates vary significantly across different socioeconomic and demographic factors, customs, cultures and practices of people living in different parts of the world. The age at first birth, one of the most significant events in a womans life, is directly and indirectly related to total fertility. The present paper is focused on the patterns, and socioeconomic and demographic determinants of age at the first birth of Myanmar women. For this study, data from the Myanmar Demographic and Health Survey 20152016 were used. A total of 7,613 ever-married women between 15 and 49 years who had given birth participated in the survey. The pattern of women at first birth was estimated using as descriptive technique and the determinants of age at first birth were identified using the Cox Proportional Hazards model. The average age at first birth of Myanmar women was 22.4 years in 2015-2016. The results of this study indicate that womens education level and their age when they first engaged in sex, birth cohort, wealth index, residence, husbands education and occupation whether they reside in a female-headed household were found to be significant factors associated with age at first birth. The age of women at first birth tended to be longer for women living in urban areas and women married to men with high degrees of education. Based on the results of this study, rural areas need to be developed and improving educational attainment is required to delay the age at first birth of women in Myanmar.